Gerakan Penghijauan Lingkungan Berbasis Tanaman Cabai dan Tomat Organik - Yoppi Darmawan; Muhamat Dandi; Endang Sulastri; Lyta Amanda; Pebri Harianto; Diah Azhari; Mujiono Mujiono; Tita Septi Handayani (Universitas Dehasen Bengkulu, 2026)
The program for distributing chili and tomato seedlings in RT 17 RW 02, Pematang Gubernur Subdistrict, is an effort to empower the community in supporting household food security and optimizing the use of home garden land. This activity aims to increase residents’ awareness and participation in independent vegetable cultivation, while also helping to meet daily food needs and reduce household expenses. The implementation methods include resident data collection, distribution of chili and tomato seedlings, and the provision of brief education on planting and plant maintenance techniques. The results of this program show high enthusiasm and positive responses from the community, as reflected in the active involvement of residents in receiving and planting the distributed seedlings. It is expected that through this program, residents of RT 17 RW 02 Pematang Gubernur will gain long- term benefits in the form of the availability of fresh vegetables, improved farming skills, and the creation of a greener and more productive environment.